The way blood dims: a novel - Dykstal, Henry Burke, author; McConigley, Nina, advisor; Altschul, Andrew, committee member; Mansfield, Mike, committee member (Colorado State University. Libraries, 2025)
The Way Blood Dims is a novel chronicling the early life of Southerncross Kite, from his boyhood raised by an artist collective in Alabama to his teen years as a member of a secret military unit in the Pacific Theatre of World War II. Blessed with an unusual appearance and a talent for violence, Kite begins to interact with the world in a story of how history shapes humanity, and how humanity shapes history.
Keywords: Japan; violence; World War II; Pacific Theatre; Alabama; war